أثر تطبيق نظام المعلومات التسويقية علي جودة الخدمات المصرفية دراسة تطبيقية على المصرف التجاري الوطني فرع /غريان (Economic studies journal, 2024)
The aim of this research is to identify the impact of applying the marketing Bank, Gharyan branch, where the focus was on the use of two dimensions of the marketing information system, namely (the internal records and reports system, and the marketing research system). The research community consisted of all the  employees working in the National Commercial Bank, Gharyan branch at all administrative levels, which numbered (44) employees, where the comprehensive  inventory method was used, and to analyze the data and test the hypotheses, the  statistical analysis program (SPSS) was used, and a set of results were reached, the  most important of which is that the bank The National Commercial Gharyan  branch has a good marketing information system, and that the most applied  dimensions in the bank in question is the system of internal records and reports,  as it turned out that there is a strong direct correlation between the marketing information system in its two dimensions (the system of internal records and  reports, the marketing research system) and the quality of banking services, and it also shows There is a statistically significant effect of the marketing information system on the quality of banking services.
Keywords: Marketing information system; quality of banking services; National commercial bank